ATTENTION TO PHYSICAL EDUCATION AND SPORTS IN THE YEARS OF INDEPENDENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, the issue of promoting a healthy lifestyle among the population and the role of sports in this has become the most active part of state policy. Over the years of independence, Uzbek wrestling has entered a completely new stage of development. On this basis, practical measures were initiated not only to develop Uzbek wrestling in our country, but also to include it in the category of international sports competitions.